2016
DOI: 10.1007/s00418-016-1509-5
|View full text |Cite
|
Sign up to set email alerts
|

Extravillous trophoblasts invade more than uterine arteries: evidence for the invasion of uterine veins

Abstract: During the first trimester of pregnancy, extravillous trophoblasts (EVTs) invade into the decidual interstitium to the first third of the myometrium, thereby anchoring the placenta to the uterus. They also follow the endovascular and endoglandular route of invasion; plug, line and remodel spiral arteries, thus being responsible for the establishment of hemotrophic nutrition with the beginning of the second trimester and invade and open uterine glands toward the intervillous space for a histiotrophic nutrition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 27 publications
2
63
0
Order By: Relevance
“…Consistent with our findings, very recently the group of Huppertz has also showed evidence for EVTs invasion of uterine veins [29], using an antibody against human leukocyte antigen (HLA)-G, often used as specific EVT marker [30]. However, caution should be taken when using only HLA-G to identify EVTs, due to the different HLA-G isoforms [31].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with our findings, very recently the group of Huppertz has also showed evidence for EVTs invasion of uterine veins [29], using an antibody against human leukocyte antigen (HLA)-G, often used as specific EVT marker [30]. However, caution should be taken when using only HLA-G to identify EVTs, due to the different HLA-G isoforms [31].…”
Section: Discussionsupporting
confidence: 87%
“…However, caution should be taken when using only HLA-G to identify EVTs, due to the different HLA-G isoforms [31]. In addition, using HLA-G immunostaining as means to identify EVTs, the same group has also reported that EVTs (coined “endoglandular”) also invaded uterine glands [29, 32, 33]. In our study, using a combination of immunofluorescence and FISH, we were unable to detect (male) EVTs in maternal uterine glands between W5.5 and W12.…”
Section: Discussionmentioning
confidence: 99%
“…Remodeling of maternal spiral arteries involves trophoblast invasion and EVT differentiation, whereby EVT forms the linings of the uterine vessels [2]. Spiral arterioles are blocked by invading endovascular trophoblasts that restrict blood flow and thereby sustain a low oxygen environment of 1–2% oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…In the placenta, some cytotrophoblasts from the column of the anchoring villi invade the maternal decidua [21]. Eventually we know that these invading trophoblasts line the spiral arteries, glands and veins and could be the source of fetal cells in maternal circulation [22]. This method of targeting EVTs has been very reliable in enriching fetal cells from every pregnant sample.…”
Section: Trophoblastsmentioning
confidence: 99%